Faktor-Faktor Yang Memengaruhi Pertumbuhan Laba Pada Perusahaan Manufaktur - Tony Sudirgo, Wanda Ribka Ivana, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This research aimed to analyze the factors affecting on earning growth of manufacturing companies which were listed on Indonesia Stock Exchange 2017-2019. This study uses four independent variables are Firm Size, Debt to Equity Ratio, Net Profit Margin, dan Total Asset Turnover. The total sample in this study was 14 companies which were determined through purposive sampling, with a total of 42 samples for three years. This study uses secondary data taken from the Indonesia Stock Exchange and uses the Eviews 12.0 data processing application. This study uses the results of statistical analysis test, classical assumption test, and multiple linear regression analysis test. The results of this study state that Firm Size, Net Profit Margin and Total Asset Turnover have no effect on the profit growth of manufacturing companies, while the Debt to Equity Ratio has a negative effect on the profit growth of manufacturing companies.